Concomitant bilateral medial malleolus stress fracture: a case report and review of literature of an extremely rare injury - Philip, Vivek Mathew; Shekhar, Raj; Sharma, Saurabh; Padhi, Prashant Pratim (International Journal of Research in Orthopaedics, 2022)
Medial malleolus stress fractures are rare stress injuries and account for 4% of all the stress fractures. Bilateral medial malleolus stress fracture (MMSFs) is extremely rare with only five such cases reported in existing literature. We report an extremely rare injury pattern in the form of concomitant bilateral MMSF in a young military recruit who presented with severe pain in both his ankles for one month. A 20-year military recruit undergoing rigorous physical training presented to us with severe bilateral ankle pain of one month duration. Clinico-radiological examination revealed bilateral MMSFs. He was managed with open reduction and internal fixation using a one-third tubular plate in buttress mode. Patient was gradually rehabilitated and on one-year follow up, he is asymptomatic and performing all strenuous physical activities. Bilateral MMSFs are extremely rare injuries with only five such cases reported in existing medical literature and this is the fourth instance where bilateral MMSFs were diagnosed at the time of clinical presentation and managed simultaneously, in the same surgical setting.